Pengaruh Pajak Kendaraan Bermotor, Bea Balik Nama Kendaraan Bermotor, Pajak Bahan Bakar Kendaraan Bermotor, dan Retribusi Parkir Terhadap Pendapatan Asli Daerah Provinsi Daerah Istimewa Yogyakarta : Pengaruh Pajak Kendaraan Bermotor, Bea Balik Nama Kendaraan Bermotor, Pajak Bahan Bakar Kendaraan Bermotor, dan Retribusi Parkir Terhadap Pendapatan Asli Daerah Provinsi Daerah Istimewa Yogyakarta - Rahmawati Nilamsari (INDONESIAN JOURNAL OF ECONOMIC AND SOCIAL SCIENCE, 2026)
Regional Original Revenue (PAD) is an important indicator of a region’s fiscal independence. One of the main contributors to PAD is the tax and retribution sector related to motor vehicles. This study aims to analyze the effect of Motor Vehicle Tax (PKB), Motor Vehicle Title Transfer Fee (BBNKB), Motor Vehicle Fuel Tax (PBBKB), and Parking Retribution on PAD in the Special Region of Yogyakarta Province. This research employs a quantitative approach using secondary data in the form of monthly realization reports from 2020 to 2024. The results show that partially, PKB, BBNKB, and PBBKB have a significant effect on PAD, while Parking Retribution does not have a significant effect. However, simultaneously, all four variables have a significant effect on PAD. This indicates that optimizing all sources of transportation-related revenue remains essential to sustainably support PAD. Keywords: PKB, BBNKB, PBBKB, Parking Retribution, PAD